Single-Dose Azithromycin versus Penicillin G Benzathine for the Treatment of Early Syphilis - Riedner, Gabriele; Rusizoka, Mary; Todd, Jim; Maboko, Leonard; Hoelscher, Michael; Mmbando, Donan; Samky, Eleuter; Lyamuya, Eligius; Mabey, David; Grosskurth, Heiner; Hayes, Richard (The New England journal of medicine, 2005)
This randomized trial involving patients with early syphilis in Tanzania found that treatment with 2 g of azithromycin led to cure rates that were similar to those for penicillin G benzathine at both nine months (97.7 percent and 95.0 percent, respectively) and six months (85.5 percent and 81.5 percent, respectively). This single-dose, oral regimen may be particularly useful in settings in which there are shortages of sterile equipment and trained personnel. In 328 patients with early syphilis in Tanzania, treatment with 2 g of azithromycin led to cure rates that were similar to those for penicillin G benzathine at both nine months and six months. A single intramuscular injection of 2.4 million units (MU) of penicillin G benzathine is the recommended therapy for early syphilis. 1 Major advantages of this regimen are its low cost and absence of problems related to poor adherence, whereas disadvantages include pain associated with large-volume (4 ml), deep, intramuscular injections; the relatively high prevalence of self-reported penicillin allergy in some settings; and the need for injection equipment and medically trained personnel, which may be lacking in countries with few health resources. In addition, there are risks of transmission of blood-borne infections, such as human immunodeficiency virus (HIV), if injection equipment is . . .